An Optimization Technique for Ranch Management - Hinojosa, Alfonso Juan; Oh, Joon-Yeoul (Journal of Applied Business and Economics, 2023)
Water is a scarce resource; it is a vital resource in the production of crops for livestock that will directly impact supply chain costs. Many costs occur in poorly deployed irrigation systems that don’t fully utilize land potential, thereby, not produce the proper yield of crops for livestock. An irrigation system can not only reduce initial set up and maintenance costs but reduces land waste while increasing yield of dry matter feed. This research presents a cost benefit analysis approach to determine the practicability of installing an irrigation system onto 54 acres of ranch land by employing the use of linear programming. Specifically, by examining factors that impact costs and production, a generalized model was developed to better understand how this system works on any ranch. These results indicate by optimizing land to its fullest capacity for dry matter, one can then maximize profits generated. This research found the profitability of employing an irrigation system is beneficial even at lower production yields when compared to land with no irrigation system.